Synovial chondromatosis caused mechanical snapping elbow: a case report - Karaman I; Guney A; Dogar F; Oner M; Bılal O (Dove Medical Press, 2015)
Ibrahim Karaman,1 Ahmet Guney,1 Fatih Dogar,2 Mithat Oner,1 Okkes Bilal3 1Department of Orthopaedics and Traumatology, Erciyes University Medical Faculty, 2Department of Orthopaedics and Traumatology, Training and Research Hospital, Kayseri, 3Department of Orthopaedics and Traumatology, Kahramanmaras Sütçü Imam University Medical Faculty, Kahramanmaras, Turkey Abstract: Synovial chondromatosis is a rare and benign proliferative disorder of the synovial membrane in joints and bursae. Herein, we present the case of a 34-year-old male with synovial chondromatosis that caused limitation in the elbow joint in terms of mechanical function. Keywords: chondromatosis, elbow, loose bodies, mechanical block